The Effect of Puzzle Playing on Smooth Motor Development in Children Aged 5-6 Years at TK. Kumara Canthi (Kindergarten) Singaraja - Mochamad Heri; Agus Ari Pratama; Putu Agus Ariana; Kadek Ayu Krisna Dewi (KHD-Production, 2022)
Preschool children are children aged 36-72 months who have their own characteristics in terms of growth and development. Every child experiences growth and development differently. Usually growth and development in preschool children is a problem that usually occurs in fine motor development. Management of smooth motor development in preschool children can be done by providing educational games such as puzzles. This study aims to determine whether there is an effect of playing puzzles on smooth motor skills in children aged 5-6 years at Kumara Canthi Kindergarten Singaraja. Pre-experimental research design with one group pretest-posttest design . The population used in this study were children aged 5-6 years in TK Kumara Canthi Singaraja. The sample size used was 34 respondents who were selected using a saturated sampling technique. Data collection techniques using Denver II and SOP puzzle. This shows that there is an Influence of Playing Puzzles on Subtle Motoric Development in Children Aged 5-6 Years in TK Kumara Canthi Singaraja.